Combined pharmacotherapy-multimodal psychotherapy in children with Disruptive Behavior Disorders. (30th April 2016) - Masi, Gabriele; Milone, Annarita; Manfredi, Azzurra; Brovedani, Paola; Pisano, Simone; Muratori, Pietro
Abstract: Although multi-component psychotherapeutic interventions are first-line treatments for Disruptive Behavior Disorders (DBD), pharmacotherapy is often associated for more severe patients. Our aim was to explore effectiveness of an associated pharmacotherapy in referred children with DBD receiving a one-year psychotherapeutic intervention. Aggression, callous unemotional (CU) traits and emotional dysregulation were outcome measures. The sample included 144 children, aged 8−12 years, 41 (29%) with an ADHD comorbidity. Fifty-five (38%) patients received an additional pharmacotherapy with one medication, methylphenidate, a second generation antipsychotic, or a mood stabilizer. Data were collected before and after the one-year treatment. According to the Child Behavior Checklist (CBCL), aggressive behaviors, rule-breaking behaviors and emotional dysregulation improved in the whole group, as well as parent- and child-reported CU traits. The hierarchical regression model showed that additional pharmacotherapy significantly predicted lower scores at the CBCL aggressive behaviors and emotional dysregulation, but not CU traits at the end of the treatment. The interaction between methylphenidate and ADHD comorbidity predicted lower aggressive behaviors after the treatment. In summary, this naturalistic investigation suggest that an additional pharmacotherapy significantly improved aggression and emotional dysregulation, but not CU traits. When ADHD was comorbid, methylphenidate was more effective than antipsychotics or mood stabilizers in reducing aggression. Highlights: Psychotherapy improved aggression, mood swings and callous unemotional traits. Additional pharmacotherapy further improved aggression and mood. Additional pharmacotherapy did not affect callous unemotional traits. In comorbid ADHD, methylphenidate was more effective than other drugs.